Trabalho e educação na mineração de nióbio em Goiás (2016-2022) - Campos, Camila Aparecida de (2022)
This doctoral thesis aims to analyze the relationship between work and education in niobium mining in Catalão and Ouvidor, municipalities in Goiás, in the last five years, the period of operation of the CMOC. Therefore, we chose to present the theoretical-methodological elaboration in thematic chapters: mining, work and education, respectively. In a fourth chapter we relate work with education through the use of the category “self-rescue zones” and we present the synthesis of the thesis that showed us that outsourced work at CMOC is more precarious due to outsourcing, and that there is no training plan for these workers who perform various functions within the industry, which, in turn, is concerned with educating society to accept mining in the current format. We also verified that the education of these workers is precarious, and there is not even a business training plan prepared for this purpose. Multifunction tasks within simplified and alienated forms of work potentiate the increase in work accidents and serious environmental disasters. What is verified is the construction of business strategies and ideologies aimed at building social consensus for the acceptance of the current forms of mining that contrasting with a precarious universe of work